The NFAT3/RERG Complex in Luminal Breast Cancers Is Required to Inhibit Cell Invasion and May Be Correlated With an Absence of Axillary Lymph Nodes Colonization - Coillard, Lucie; Guaddachi, Frédéric; Ralu, Maëlle; Brabencova, Eva; Garbar, Christian; Bensussan, Armand; Le Bras, Morgane; Lehmann-Che, Jacqueline; Jauliac, Sébastien (Frontiers in Oncology, 2022)
Luminal breast cancers represent 70% of newly diagnosed breast cancers per annum and have a relatively good prognosis compared with triple negative breast cancers. Luminal tumors that are responsive to hormonal therapy are particularly associated with a favorable prognosis. Nonetheless, the absolute number of metastatic relapses in luminal cancers is larger than in triple negative breast cancers. A better understanding of the biology of luminal cancers, control of metastases formation and identification of predictive markers of their evolution are therefore still necessary. In this context, we previously disclosed the key role of NFAT3 in regulating luminal breast cancer invasion. We have now identified a specific inhibitory region, in the C-terminal part of NFAT3, required for the inhibition of invasion of the human luminal breast cancer cell line T-47D. Indeed, we showed that this 85 amino acids C-terminal region acts as a dominant negative form of NFAT3, and that its over-expression in the T-47D cell line led to increased cell invasion. Mechanistically, we have revealed that this region of NFAT3 interacts with the small Ras GTPase RERG and shown that RERG expression is required for NFAT3 to impede T-47D cell invasion. We have validated the association of NFAT3 with RERG in human luminal breast cancer tissues. We have shown an increase of the quantity of the NFAT3/REG complexes in patients without axillary lymph nodes colonization and therefore proposed that detection of this complex may be a noninvasive marker of axillary lymph nodes colonization.